STRATEGI IMPLEMENTASI NILAI KEJUJURAN, KEDISIPLINAN DAN TANGGUNG JAWAB GURU PENDIDIKAN KEWARGANEGARAAN DI SEKOLAH DASAR - Ventura, Bona; Marzuki, Marzuki; Marli, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis study aimed to describe the Implementation of Honesty value, Discipline value and Responsibility value of Civic Education Teachers through strategy implementation of Honesty value, Discipline value and Responsibility value of civic education teacher at Elementary School Pontianak Timur. This research is a descriptive qualitative approach. Subjects in this study were teachers and students of fifth class State Elementary School 09, State Elementary School 10 and State Elementary School 16 at Pontianak Timur. The data collection is done by observation, interview and documentation. Data analysis is done through the following phases: data reduction, data display, and conclusion. The method examination of the validity data by using triangulation. The results of this study indicate that the strategy implementation of Honesty value, Discipline value and Responsibility value of civic education teacher at Elementary School Pontianak Timur its exemplary of civic education teacher, and habituation in the learning activities are done continuously so that the impact on the formationÂ character noble of learners.Â Keywords: Strategy Implementation, Civic Education Teachers, Honesty Value, Discipline value, Responsibility ValueÂ